Does Perceived Nuisance Abundance of Water Plants Match with Willingness-to-Pay for Removal? Contrasts Among Different User Categories - Jan E. Vermaat; Kirstine Thiemer; Bart Immerzeel; Susanne C. Schneider; Keneilwe Sebola; Julie Coetzee; Antonella Petruzzella; Samuel N. Motitsoe; Mathieu Baldo; Benjamin Misteli; Gabrielle Thiébaut; Sabine Hilt; et al. (Environmental Management, 2025)
Dense beds of water plants can be perceived as nuisance, but this perception, however, may not be similar for different user categories, and this may affect their willingness-to-pay (WTP) for plant removal. A questionnaire survey was used to test this for residents and visitors and find underlying socio-cultural or economic drivers. We studied five cases where nuisance water plant growth is managed: the rivers Otra (Norway) and Spree (Germany), and the lakes Kemnade (Germany), Grand-Lieu (France), and Hartbeespoort Dam (South Africa). We used a different payment vehicle for residents (annual household tax) and visitors (tourist tax). The survey included questions on days spent on specific types of activity per year, the importance attached to different functions and activities, overall environmental attitude, perception of the plants, socio-demographic respondent characteristics and WTP for increased plant removal. We observed no increase in WTP for increased removal in most sites. The two most important drivers of variation in current WTP were income, and whether respondents were engaged in boating and angling and thus perceived the plants negatively. Variation in WTP among sites was considerable, and mainly related to the mixture of activities among respondents. Differences between residents and visitors were less important than those among sites. Our observations bear importance for water management: information on differences in experienced nuisance among user categories and the frequency of use by these categories is useful as guidance for the design and implementation of any plant removal plan.